Mikroenkapsulasi Propanolol Hidroklorida Dengan Penyalut Etil Selulosa Menggunakan Metoda Penguapan Pelarut - Sutriyo, Sutriyo; Djajadisastra, Joshita; Novitasari, Adilla (Majalah Ilmu Kefarmasian, 2004)
Propranolol hydrochloride is antihypertension agent that has a short biological half life of 2-6 hours. Microcapsules of propranolol hydrochloride are prepared by solvent evaporation method using ethylcellulose as a wall material with the drug-polymer ratio 1:1, 1:2, and 1:3 for sustained release oral delivery. The microcapsules were then evaluated by particle size distribution analysis, shape and morphology (SEM), drug content, and dissolution studies. In vitro dissolution was studied using the dissolution apparatus II (paddle) with chloride buffer (pH 1,2) dan phosphate buffer (pH 6,8) medium. The drug-polymer ratio have an important influence on drug release from microcapsules where the increase of polymer cause the higher drug release inhibition.